Photobiomodulation as an adjunct in the treatment of acute lung injury due to sepsis (Research, Society and Development, 2020)
Sepsis is considered a major health problem, with acute lung injury (ALI) being one of the most serious complications of septic shock. It is known that an ALI is a disease characterized by damage to the alveolar epithelium, infiltration of inflammatory cells, increased permeability of the alveolar - capillary barrier, interstitial edema that cause an imbalance in the condition and pulmonary perfusion, with a high morbidity rate and in the units intensive care. The treatment of ALI has a high cost and is often not sufficiently effective and, therefore, the search for new therapies is of extreme clinical importance. Photobiomodulation (PBM) through lasers and LEDs has to be a promising tool with good results for several inflammatory diseases, including changes that affect the respiratory system. Within this context, the objective of this study is to provide, through a narrative review, an understanding of the current available evidence on the importance of PBM in the treatment of respiratory disorders and its possible applicability in ALI due to sepsis. The searches were performed in the bibliographic databases of PubMed / MEDLINE, Virtual Health Library (VHL), Web of Science and SciELO. The evidence found in this study points out that PBM can be proposed as a support for conventional medical therapy in the treatment of ALI arising from sepsis, due to the potential to prevent the progression of lung parenchyma injury, attenuate the inflammatory condition, reduction process and reduce the recovery time of the patient with APL due to sepsis.